Evaluation and Design of Supply Chains for Bioenergy Production - Daniel José Bernier-Oviedo; Alexandra Eugenia Duarte; Óscar J. Sánchez (Energies)
Future energy security and consumption trends for energy products have stimulated the consumption of products such as bioethanol, biodiesel, or biogas, generated from non-petroleum sources. Therefore, the production of these products aims to increase its viability progressively. The supply chain (SC) approach enables the evaluation of the structures used to produce these types of bioenergy. Consequently, the identification of tools to represent the production stages of the SC and their articulation with the objective functions, as well as the strategies and solution software implemented in the design of SC for bioenergy products are presented throughout this bibliographic analysis. Based on systematic and narrative literature analysis, current trends and future research issues are performed. The bibliographic analysis has evidenced that the production of bioenergy is a research topic that has evolved in the last decades. Strategic decisions such as factory capacity and the location of production facilities are the most frequently used decision variables in the design of bioenergy SC. Similarly, it was found that the bioenergy SC designs have focused on the implementation of several feedstocks simultaneously. Finally, due to these evaluation and design trends, the bioenergy SC designs that include environmental and social objectives aimed at sustainability are a future relevant research issue.